Liability of Internet Intermediary in The Indian Context: A Comparative Overview of Their Challenges With Reference to US And UK - Nehaluddin AHMAD; Saurabh CHATURVEDI; Supri Hj SUDIN (Communications of International Proceedings, 2021)
The internet has transformed the economics of communication, creating a spirited debate as to what is the liability of internet intermediaries like internet service providers in India. Existing liability schemes generally join traditional fault-based liability rules to broad internet-specific liability exemptions. Internet intermediaries, on the other hand, are easy to identify and have permanent commercial roots inside the jurisdictions that seek to regulate the internet. Further, these internet intermediaries are essential to most of the transactions on which the internet pirates rely. The article aims at evolving an ideal regime for the position of internet intermediaries in India after making a comparative study of existing laws in the United States, the United Kingdom. The article also points out the protection and immunity that the Indian Information Technology Act provides for intermediaries.